Virtual Reality and Assistive Technologies: A Survey - Yasmin, Shamima (International Journal of Virtual Reality, 2018)
This paper conducts an extensive survey on existing Virtual Reality (VR)-based rehabilitation approaches in the context of different types of impairments: mobility, cognitive, and visual. Some VR-based assistive technologies involve repetitions of body movements, some require persistent mental exercise, while some work as sensory substitution systems. A multi-modal VR-based environment can incorporate a number of senses, (i.e., visual, auditory, or haptic) into the system and can be an immense source of motivation and engagement in comparison with traditional rehabilitation therapy. This survey categorizes virtual environments on the basis of different available modalities. Each category is again subcategorized by the types of impairments while introducing available devices and interfaces. Before concluding the survey, the paper also briefly focuses on some issues with existing VR-based approaches that need to be optimized to exploit the utmost benefit of virtual environment-based rehabilitation systems .